Geomorphometric Analysis of Submarine Mud Volcanoes: Variability, Evolutionary Trends, and Geohazard Implications - Simone Napoli; Daniele Spatola; Daniele Casalbore; Francesco Latino Chiocci (Journal of Marine Science and Engineering)
The systematic morphometric analyses of submarine mud volcanoes are widespread yet still poorly understood geological features. Our study reveals that submarine mud volcanoes show significant variability in size and geometry, independent of water depth. Specifically, the mean height-to-radius (H/R) ratio is ~0.14 ± 0.08 (±1σ). This study focuses primarily on submarine mud volcanoes in the Mediterranean, which account for approximately 58% of the dataset and include structures reaching heights of up to ~500 m with mean diameters of up to 8000 m. These edifices display a range of basal geometries, from sub-elliptical (e.g., North Alex, off the coast of Egypt) to super-elliptical (e.g., Alberto da Ottaviano in the Mediterranean Ridge Accretionary Complex). A comparative analysis of morphometric parameters distinguishes mud cones from mud pies globally, with the latter generally lacking large examples (mean diameter >10 km). The results suggest distinct evolutionary pathways, beginning with small simple cones (~100 m3 in volume), analogous to arc volcanoes in other geological settings. This study integrates fundamental marine geology with applied geohazard considerations, serving as an initial step toward enhancing shared knowledge of submarine mud volcanoes. By improving the understanding of their formation, morphometric variability, and spatial distribution, this research supports better-informed decisions regarding submarine geohazards.